Examining the levels of acetylation, DNA methylation and phosphorylation in HIV-1 positive and multidrug-resistant TB-HIV patients. (December 2020) - Marimani, Musa; Ahmad, Aijaz; Stacey, Sarah; Duse, Adriano
Highlights: Epigenetic modifications alter gene expression patterns in patients with MDR TB and HIV-1 co-infection and HIV-1 positive. Expression of HAT, HDAC, PtkA and PtpA genes were substantially increased in HIV-1 infected than MDR TB-HIV co-infected. Differential gene expression can be employed to produce new therapies and vaccines capable of eliminating co-infections. Abstract: Objectives: In this study, we examined the impact of epigenetic modifications on host gene functioning by assessing the expression of seven candidate genes in three separate groups including healthy, multidrug-resistant (MDR) TB-HIV co-infected and HIV-1 positive individuals. Methods: Ten patients with MDR TB and HIV-1 co-infection on TB and HIV therapy and a cohort comprised of 10 newly diagnosed individuals with HIV-1 infection were recruited from the TB and HIV clinics at the Charlotte Maxeke Johannesburg Academic Hospital. Notably, the HIV-1 positive individuals were not placed on antiretroviral therapy (ART) at the time of recruitment and blood collection. A third group consisting of 10 healthy participants without MDR TB or HIV infection was recruited from the University of the Witwatersrand. Blood samples collected from all three cohorts were employed for extraction of plasma, total RNA and genomic DNA. Results: Our data indicated that the expression of DNA methyltransferase 1 ( DNMT1 ) and Ten-eleven translocation methylcytosine dioxygenase 1 ( TET1 ) genes was significantly increased in HIV-1 positive patients and was lowest in MDR TB-HIV co-infected patients. By contrast, histone acetyltransferase ( HAT ), histone deacetylase ( HDAC ), protein tyrosine kinase ( PtkA ) and protein tyrosine phosphatase ( PtpA ) mRNA expression levels were substantially enhanced in HIV-1 infected and were lowest in healthy individuals. Conversely, Dicer expression levels were comparable among all three study groups. Conclusion: Promising preliminary data emanating from this investigation may potentially be used for generation of novel vaccines and therapeutic compounds capable of neutralising MDR TB-HIV and HIV-1 infection.